KAJIAN YURIDIS TERHADAP PERLINDUNGAN PIHAK TERTANGGUNG ASURANSI KESEHATAN PADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI SAMARINDA - Titi Riskana (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT This research entitled "A Juridical Study of the Protection of the Insured Person in Health Insurance at the Social Security Administering Body (BPJS) in Samarinda",The purpose of this study is to know clearly about the arrangements in order to protect the insured health insurance in the event of a claim that is greater than that covered by the health social security administering agency (BPJS), and aims to find out what efforts should be made by the government against the insured party of the health social security administering body (BPJS) to resolve claims that are greater than the insured amount.This research is a type of research that is normative in nature. The type of data used is primary data in order to obtain library materials and regulations related to the title of the thesis. The data collection technique used was carried out by literature study. In this case, what is examined is the implementation and payment of health insurance claims in the event of a claim that is greater than that covered by BPJSA health according to Law Number 40 of 2004 concerning the National Social Security System (SJSN).From the results of the study, it can be concluded that the implementation of payment for health insurance claims from health providers is greater than the insured, BPJS health is usually verified first by the BPJS Kesehatan by checking and studying written notifications from health service providers (PPK), BPJS health officers. come to PPK to verify the amount of claims borne by BPJS Kesehatan, check supporting evidence of claims submitted by PPK, and pay insurance claims in accordance with the verification results as well as efforts that must be made by the government to protect the insured party of BPJS Kesehatan to overcome claims of health providers that are larger than those be insured, namely making regulations on BPJS health by fostering a health service system that is efficient, effective and accountableKeywords: BPJS, Health Insurance and Claims Implementation.